El método Robinson en el proceso del desarrollo del aprendizaje, en los niños de 6 a 8 años de la Fundación “Emanuel” de la ciudad de Riobamba periodo académico 2023-2024 1S. - Garcés Armas, Shirley Dayana (2024)
The research highlights the relevance of the Robinson Method as an effective educational tool to enhance the development of learning, specifically reading in children from 6 to 8 years old belonging to the Emanuel Foundation of the city of Riobamba. The detailed methodological approach and encouraging results reinforce the idea that this method not only improves reading, but also plays a crucial role in the comprehensive development of children's learning. This research explores the positive influence of the Robinson Method on children's reading development, focusing on aspects such as verbal fluency, vocabulary and linguistic comprehension. The methodology, descriptive, mixed and non-experimental, combines bibliographic and field elements to comprehensively analyze the impact of the method on children's linguistic development. The results obtained reveal significant observable changes in the reading skills of the participating children, as well as quantitative data on the teachers' perception in relation to the development of reading and general learning in the children. These findings suggest that the applied method is not only an effective strategy to optimize reading techniques, but also has a positive impact on children's general learning development.